2008
DOI: 10.1093/jn/138.8.1417
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Quercetin in Pigs after Long-Term Dietary Supplementation

Abstract: Although the flavonol quercetin is intensively investigated, our knowledge about its bioavailability and possible target organs is far from being complete. The aim of this study was to check the potential of quercetin to accumulate in various tissues after long-term dietary treatment compared with a single treatment with flavonol. Pigs ingested either a single dose of quercetin aglycone (25 mg/kg body weight; Expt. 1) or received the flavonol twice a day at the same dose mixed into their regular meals (i.e 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 17 publications
6
115
0
8
Order By: Relevance
“…None of the investigated extracts increased the concentrations of total phenols in the muscle, and therefore meat from pigs fed flavonoids and phenolic-enriched diets had similar TBARS values as meat from pigs fed a control diet, but significantly higher than meat from pigs fed α-tocopherol-enriched diets. Very low concentration of quercetin in the LD muscle of pigs was also reported by Bieger et al (2008) who did not observe any direct antioxidant effect of flavonols in meat, relevant for post-mortem storage and stability. The largest amounts of quercetin were noted in the organs involved in metabolism, and quercetin concentration was higher in the blood plasma than in the LD muscle.…”
Section: Discussionsupporting
confidence: 67%
“…None of the investigated extracts increased the concentrations of total phenols in the muscle, and therefore meat from pigs fed flavonoids and phenolic-enriched diets had similar TBARS values as meat from pigs fed a control diet, but significantly higher than meat from pigs fed α-tocopherol-enriched diets. Very low concentration of quercetin in the LD muscle of pigs was also reported by Bieger et al (2008) who did not observe any direct antioxidant effect of flavonols in meat, relevant for post-mortem storage and stability. The largest amounts of quercetin were noted in the organs involved in metabolism, and quercetin concentration was higher in the blood plasma than in the LD muscle.…”
Section: Discussionsupporting
confidence: 67%
“…In fact, quercetin has a powerful antioxidative capacity. tissues even though oral supplemented in rats or pigs [3,7].…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenol feeding studies on pigs have found polyphenols at micromolar concentrations in a variety of tissues and organs (Bieger et al, 2008;Kalt et al, 2008;Kalt et al, 2007), but one concern with these studies is that entrained blood may not have been completely removed, thus casting doubt on the actual concentrations in the tissues. On balance, it seems probable that polyphenols can access tissues and therefore cells in vivo, but probably in the form of conjugated metabolites or breakdown products, rather than the unconjugated forms tested in vitro.…”
Section: Bioavailability and Access Of Polyphenols To Mitochondria Inmentioning
confidence: 99%